Caloric restriction: Impact upon pituitary function and reproduction - Martin, Bronwen (2008)
Reduced energy intake, or caloric restriction (CR), is known to extend life span and to retard age-related health decline in a number of different species, including worms, flies, fish, mice and rats. CR has been shown to reduce oxidative stress, improve insulin sensitivity, and alter neuroendocrine responses and central nervous system (CNS) function in animals. CR has particularly profound and complex actions upon reproductive health. At the reductionist level the most crucial physiological function of any organism is its capacity to reproduce. For a successful species to thrive, the balance between available energy (food) and the energy expenditure required for reproduction must be tightly linked. An ability to coordinate energy balance and fecundity involves complex interactions of hormones from both the periphery and the CNS and primarily centers upon the master endocrine gland, the anterior pituitary. In this review article we review the effects of CR on pituitary gonadotrope function and on the male and female reproductive axes. A better understanding of how dietary energy intake affects reproductive axis function and endocrine pulsatility could provide novel strategies for the prevention and management of reproductive dysfunction and its associated comorbidities.